The Effect of Tax Amnesty, Service Quality, And Taxpayer Awareness On Motor Vehicle Tax Compliance - Andriyanti, Nada Ilvian (DIPONEGORO UNIVERSITY, 2025)
This study aims to analyze the influence of the tax amolishment program, the quality of tax services, and taxpayer awareness on motor vehicle tax compliance in Boyolali Regency. The data collection method used a questionnaire. The sampling technique used purposive sampling. The sample size used was 101 respondents. The results showed that the tax amolishment program partially had no effect on taxpayer compliance. Meanwhile, service quality and taxpayer awareness partially had a positive effect on taxpayer compliance in paying motor vehicle tax.